Frågan om organdonation: Anhörigas och internsivvårdsläkares erfarenheter och attityder - Sanner, Margareta (Socialmedicinsk tidskrift, 2007)
Syftet med den studie som presenteras här var att studera hur anhöriga och läkare förstod situationen när organdonation aktualiserats vid ett dödsfall, samt vilka faktorer som var avgörande för beslut om donation i dessa fall. Läkare till 24 avlidna patienter samt 20 anhöriga till dessa patienter intervjuades. Intervjuerna analyserades med kvalitativ metodik. Elva av patienterna hade själva bestämt hur de ville ha det; i 14 fall fick anhöriga avgöra frågan. Hälften av dessa anhöriga sa ja till donation och hälften nej. För familjen var dock donationsfrågan sekundär; de var helt upptagna av dödsfallet och försökte initialt undvika frågan genom att behandla ett nej som ett ”icke-beslut”. De behövde stöd för att olustreaktioner skulle avklinga, för att orka tänka rationellt och fatta ett välgrundat beslut. Förutsättningen för att ta upp frågan var ändå god: anhöriga hade förberetts väl för det stundande dödsfallet genom fortlöpande information från läkarna, de kände förtroende för vården, accepterade att donationsfrågan togs upp och förstod innebörden av hjärnrelaterade dödskriterier. Ungefär hälften av läkarna upplevde dock konflikter när det gällde att ta upp frågan och tala med de närstående. Tre olika förhållningssätt identifierades: pro-donation, neutralt och ambivalent. Endast läkare med pro-donationsinriktning fick ja till donation av de närstående. The aim of this study was to explore how relatives and physicians in cases where organ donation had been requested understood this situation and what factors were salient for the decision on donation. Physicians of 24 deceased patients and 20 relatives were interviewed. The material was analysed using qualitative methods. Eleven patients had declared their wishes on donation prior to death; in 14 cases the relatives had to decide. Half of these relatives accepted donation and half refused. The donation request was of secondary importance to the families; they were totally occupied by the death and initially tried to avoid the request by regarding “no” as a non-response. They needed support to relieve their immediate reactions of uneasiness, start rational thought processes and reach well-grounded answers. The basis for requesting donation was good; relatives had, with regard to circumstances, been well prepared for the death by continuous information from the physicians and had confidence in staff, accepted that the question was raised, and understood the death criteria. However, about half the physicians experienced conflicts regarding prerequisites of procuring organs and dealing with relatives. Three different approaches were displayed: pro-donation, neutral and ambivalent. Only physicians with a pro-donation approach received acceptance for donation. Key words: organ donation, transplantation, attitudes, intensive care physicians, relatives, organ donor.